A new damage detection method of single-layer latticed shells based on combined modal strain energy index. (1st June 2022) - Zhang, Yujian; Luo, Yongfeng; Guo, Xiaonong; Li, Yunsong
Highlights: The matching-combination method of vibration modes is developed to construct the combined vibration mode. The combined modal strain energy index is proposed based on the difference between the original mode and the combined mode. The results of numerical examples show that the proposed method features high damage localization accuracy. Abstract: The existing damage detection methods are challenging to be directly applied to single-layer latticed shells due to the complex mechanical mechanism and modal characteristics of such structures. In this regard, an effective damage detection method based on the combined modal strain energy index is proposed in this paper to detect the location of the damaged members in such structures. Based on the vibration modal features before and after damage of structures, the modal matching and combination method is presented to generate the combined mode, which include the modal matching procedure based on the modal assurance criterion and the modal combination procedure using the Kriging interpolation. Compared with the damaged mode, the specially constructed combined mode can significantly reduce the mode shape discrepancy in the undamaged region on the basis of retaining the characteristic differences in the damaged members. On this basis, the combined modal strain energy change index is proposed according to the modal strain energy difference between the original mode and the combined mode. Since the proposed index is established according to the difference between the combined vibration mode and the original vibration mode, the values of damage index of the undamaged members are greatly reduced, so as to effectively avoid the occurrence of misjudgement. Several numerical examples with different damage scenarios are studied in order to evaluate the proposed approach. The results clearly indicate that the proposed method features high damage localization accuracy compared with traditional methods and good measurement noise robustness.